2011
DOI: 10.1371/journal.pone.0022825
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Campylobacter amongst a Free-Range Broiler Breeder Flock Was Primarily Affected by Flock Age

Abstract: Campylobacter successfully colonizes broiler chickens, but little is known about the longer term natural history of colonization, since most flocks are slaughtered at an immature age. In this study, the prevalence and genetic diversity of Campylobacter colonizing a single free-range broiler breeder flock was investigated over the course of a year. The age of the flock was the most important factor in determining both the prevalence and diversity of Campylobacter over time. There was no correlation with season,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…The absence of recombination between coexisting host generalists living in the same hosts is surprising as they appear to share identical ecological strategies being routinely isolated from the same cattle herd ( Sproston et al. 2011 ), or chicken flock ( Colles et al. 2011 ; Jorgensen et al.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of recombination between coexisting host generalists living in the same hosts is surprising as they appear to share identical ecological strategies being routinely isolated from the same cattle herd ( Sproston et al. 2011 ), or chicken flock ( Colles et al. 2011 ; Jorgensen et al.…”
Section: Resultsmentioning
confidence: 99%
“…Predominant STs at a particular farm have been reported in several studies [29–31], and experimentally some strains are able to become dominant within a confined host-species population [32]. One study identified age of flock broilers as the most important factor correlated with increasing genetic diversity of Campylobacter , implying that genetic clones can accumulate within the flock and persist [33]. It is unlikely that the greater MLST diversity on Farm A compared to Farm B observed in this study reflects any difference in age of flock broilers or length of time these farms have been in production.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of birds shedding Campylobacter in faeces depends on the age and specie of the bird. A study conducted in broilers under semi‐intensive systems reported an increase in Campylobacter prevalence from 20% in week 5 to 88% in week 11 of age, after that the prevalence averaged 40% until week 63 (Colles, McCarthy, Layton, & Maiden, ). In free‐range ducks, the opposite was observed whereby faecal shedding was reported to be significantly higher in adult ducks than in ducklings (Nonga & Muhairwa, ).…”
Section: Campylobacter Colonization and Shedding In Birdsmentioning
confidence: 99%